Mutagenicity and Amounts of Polycyclic Aromatic Hydrocarbons in Marijuana Smoking Tar Extracted from Pipes - Shimizu, Hidesuke; Ando, Hiroaki; Hayashi, Kazuo; Suzuki, Yuji (Nippon Eiseigaku Zasshi (Japanese Journal of Hygiene), 1992)
In spite of strict laws prohibiting it, criminal cases involving marijuana abuse are increasing, resulting in a serious social problem in Japan. The most common method of ingestion is smoking, since abusers feel that this method produces quick psychological effects controversial. Marijuana is known to induce psychological addiction, but it's genotoxic effects are still argued. Marijuana smoking tar has been extracted from seized pipes. The amounts of polycyclic aromatic hydrocarbons (PAH) in the tar were weighed and the mutagenic activity was tested. The results are as follows: 1) Five of the seven PAHs were detected in marijuana tar, although benzo (e) pyrene and perylene were not. 2) There was more pyrene than any other substance detected in the tar, with fluoranthene having the next highest concentration. 3) Mutagenic activity was observed in all samples, with relative mutagenic potency ranging from 0.03 to 1.59. 4) The type of smoking pipe and burning temperature may affect the mutagenic activity and the amount of PAH. 5) Since marijuana smoking tar contains carcinogens, promoters, and mutagens, there is a risk of developing cancer just as in the case of tobacco.